Empirical Relationship between Gender Equality and Socio-economic Developments: An Error Correction Model - Uswatun Khasanah; Hadi Sasana (Arthatama: Journal of Business Management and Accounting, 2022)
Gender equality is to obtain equal opportunities without gender differences and equality in their rights to feel the results of development. The low gender will trigger injustice, where one gender will be harmed. This form of gender injustice often occurs through stereotyping, labeling, subordination, marginalization, and double burdens, which usually will harm women. This study aims to determine the active contribution of women to the world economy and to see how big the role of women in improving the economy from the political realm is carried out using the ECM-EG approach and sample time series data from 1990-2018 in Indonesia. The results showed positive effects of education, health, and representation in the political field on gender equality. The findings theoretically suggested further research on gender in employment runs by the fast-slow pattern of the legal process of The Law of Diminishing Return (TLDR), which is very influential by the quality of human resources and technological advances as well as the employment opportunities needed by women.